Lai Kwan remains a force - Ishak, Fadhli (2012)
FORMER national swimmer Chui Lai Kwan showed her pedigree by sweeping three gold medals on the first day of the swimming competition at the inaugural Malaysian Institutions of Higher Learning Games (SUKIPT) yesterday.